Optical Fiber Communication Evolution,Technology and Future Trends - Dasari, Anusha (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2015)
Fiber optic systems are important telecommunication infrastructure for world-wide broadband networks. Wide bandwidth signal transmission with low delay is a key requirement in present day applications. Optical fibers provide enormous and unsurpassed transmission bandwidth with negligible latency, and are now the transmission medium of choice for long distance and high data ratetransmission in telecommunication networks. This paper gives an overview of fiber optic communication systems including their key technologies, and also discusses their technological trend towards the next generation.